Financial Management and E-Commerce Training in Steps to Increase Revenue at Abah Ukar Blacksmith in Tasikmalaya - Gina Nuraini; Grida Saktian Laksito (International Journal of Research in Community Services, 2021)
The implementation of financial management and marketing training through E-commerce is a form of community service, with the aim of helping SMEs Blacksmith Abah Ukar to increase revenue and product sales so that Blacksmith Abah Ukar can survive in today's business competition. The era that uses technology today requires all small industry players to improve their abilities in the field of communication and information technology, currently internet-based technology creates a business environment that is no longer concerned with time and distance. This method of community service activity has a background problem because the products made by the blacksmith Abah Ukar are still sold conventionally and have not made good use of online sales using an e-commerce platform and the blacksmith Abah Ukar has not kept a record of their production so that the income earned cannot be well predicted. The results of the research carried out were able to innovate marketing which was originally conventional into marketing that utilizes technological developments, namely by doing electronic marketing or also called E-commerce.